Peran Transparansi Dalam Memoderasi Pengaruh Tax Avoidance, IOS dan Profitabilitas Terhadap Nilai Perusahaan - Safaah, Nailis; Pratama, Abdul Aziz Nugraha (AKTSAR: Jurnal Akuntansi Syariah, 2023)
This research aims to analyze and determine the effect of tax avoidance, investment opportunity set (IOS), and profitability on company value by using company transparency as a moderating variable. This type of research is quantitative with panel data obtained from secondary data from financial reports that have been published on the website www.idx.co.id. The research sample was filtered using a purposive sampling technique with several predetermined criteria, and then 35 manufacturing companies registered with ISSI for the 2019-2021 period were produced that met the criteria so the total sample used was 105 samples. After testing with the Eviews 9 tool, the results showed that the tax avoidance variable had no effect on company value, IOS had a positive and significant effect while profitability had a positive but not significant effect. Meanwhile, company transparency is only able to moderate the relationship between IOS and company value, tax avoidance and profitability variables cannot be moderated by transparency in influencing company value. Keywords: Tax Avoidance; IOS; Profitability; Firm Value; Firm Transparency